Pengaruh Fraud Pentagon, Efikasi Diri dan Penyalahgunaan Teknologi Informasi Terhadap Kecurangan Akademik pada Pembelajaran Daring (Studi pada Mahasiswa Akuntansi Kota Malang) - Dian Anjani; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2023)
This research's purpose is to work out the influence of fraud pentagon, self-efficacy, and Abuse of Information Technology on Academic Fraud in online learning. This study may be a quantitative study with corelational research characteristics using primary data obtained from questionnaires and measured using the Likert Scale. The population during this study were Accounting Students Faculty of Economics and the Business in Malang city from State University of Malang, State Polytechnic of Malang. and University of Merdeka Malang. Sampling using the Slovin formula obtained the final result for as many as 110 respondents. The strategy of determining the sample is simple random sampling. This data analysis technique used is Multiple Linier Regression Analysis with SPSS 22.0 for windows. The results of the research show: 1) The variable of the Fraud Pentagon (Rationalization, Pressure, Opportunity, Arrogance, Ability), Self -Efficacy and Abuse of Information Technology influence simultaneously on Academic Fraud on the online learning, 2) consistent with the t-test, the variable of Pressure, Opportunity, and Abuse of Information Technology have a partial influence on fraud academic in the online learning 3) consistent with the t-test, the variable of Rationalization, Arrogance, Ability, and Self- Efficacy haven't any partial influence on Academic Fraud in the online learning.Keywords: Fraud Pentagon, Self- Efficiacy, Abuse Information Technology, Academic Fraud, Online Learning.